The Genome Sequences of Baculoviruses from the Tufted Apple Bud Moth, Platynota idaeusalis, Reveal Recombination Between an Alphabaculovirus and a Betabaculovirus from the Same Host - Robert L. Harrison; Michael A. Jansen; Austin N. Fife; Daniel L. Rowley (Viruses)
The USDA-ARS collection of insect viruses at Beltsville, MD, USA, contains samples of an alphabaculovirus from larvae of the tufted apple bud moth, Platynota idaeusalis Walker, as well as a presumptive betabaculovirus from the same host species. The viruses in these samples—Platynota idaeusalis nucleopolyhedrovirus isolate 2680 (PlidNPV-2680) and Platynota idaeusalis granulovirus isolate 2683 (PlidGV-2683)—were characterized by electron microscopy of their occlusion bodies (OBs) and determination and analysis of their genome sequences. Scanning and transmission electron microscopy of the OBs revealed morphologies typical for alphabaculoviruses and betabaculoviruses. Sequencing viral DNA resulted in circular genomes of 121,881 bp and 106,633 bp for PlidNPV-2680 and PlidGV-2683, respectively. Similar numbers of ORFs (128 for PlidNPV-2680, 125 for PlidGV-2683) were annotated, along with ten homologous regions (hrs) in the PlidNPV-2680 genome and five intergenic regions of tandem direct repeats (drs) in the PlidGV genome. Phylogenetic inference from core gene alignments suggested that PlidMNPV-2680 represents a unique lineage within the genus Alphabaculovirus, while PlidGV-2683 was grouped with clade b betabaculoviruses. A comparison of the PlidNPV-2680 and PlidGV-2683 genomes revealed a 1516 bp region in PlidNPV-2680 that exhibited 97.5% sequence identity to a region of the PlidGV-2683 genome, suggesting that recombination had occurred recently between viruses from these lineages.